Effect of a brief episode of experimental muscle pain on jaw movement and jaw‐muscle activity during chewing. (22nd December 2016) - Inamoto, Kyoko; Murray, Greg M.; Whittle, Terry
Abstract : The aims of this study were to determine whether: (i) the jaw motor system develops a new pattern of jaw movement and/or jaw‐muscle activity after resolution of an acute episode of jaw‐muscle pain; and (ii) if jaw‐muscle activity and jaw‐movement features change progressively with repetition of a chewing sequence. Jaw movement and jaw muscle (masseter, anterior temporalis, and digastric) activity were recorded during free and rate‐standardized chewing in eight asymptomatic participants (pain infusion group), before and at three time blocks up to 45 min after a single 0.2‐ml bolus infusion of 5% hypertonic saline into the right masseter muscle. The same procedure, without infusion, was performed in another eight participants (control group). There were no significant main effects of group on jaw movement and muscle activity, suggesting that there were no persistent post‐pain effects on chewing. Across groups, repetitions of free and unstandardized chewing movements were associated with progressive increases in velocity and amplitude of jaw movement and masseter and temporalis electromyographic (EMG) activity. These findings suggest that factors unrelated to pain, such as practice effects, may be playing a role in the changes in jaw movement and jaw‐muscle activity observed after resolution of an acute episode of jaw‐muscle pain.